Fetal Resorption In Asian Jackal (Canis Aureus) - A Case Report - Kamdi, B. P.; Kulurkar, P. M.; Sonkusale, P. M.; Pande, R.; Raut, S.; Bhandarkar, A. G.; Kurkure , N. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Asiatic jackal typically inhabits lowlands on the outskirts of towns, villages and farms, where they shelter in holes among ruins or dense brush. In animals, pregnancy loss may occur at any stage of gestation. Sometimes, there is failure of an aborting fetus to be expelled perhaps due to uterine inertia and intrauterine infections resulting in fetal emphysema and maceration (Jhonston et al., 2001). Under the circumstance, bacteria enter the dilated cervix and the soft tissues are digested by putrefaction and autolysis leaving a mass of foetal bones within the uterus. These bones may be embedded within the uterine wall resulting in a chronic endometritis and severe damage to the endometrium (Ate et al., 2011). The most common causes of both fetal resorption and abortion are fetal defects, abnormal maternal environment, infectious agents, i.e., Brucella, Canine herpes virus infection, trauma and inadequate progesterone level in mother. The cases of foetal resorption have been reported from many species of domestic animals but reports are rare in case of wild animals.